Caffeine as an Ergogenic Aid: Enhancing Power Output in Wrestlers - Salsabila, Syafira; F. Syihab, Syifa; Rizki Sentani, Muchamad; Puspita Prameswari, Fajria Saliha (Journal of Sport Science and Fitness, 2025)
Introduction: Caffeine is known as an ergogenic aid that can enhance sports performance by stimulating the central nervous system and reducing perceived fatigue. Objectives: This study aims to determine the effect of caffeine consumption on increasing upper body power in wrestling athletes. Method: This research employed an experimental design with a pre-test and post-test approach on two groups: an intervention group (n=13) that consumed caffeine at a dose of 3–6 mg/kgBW and a control group (n=13) that consumed a placebo. Upper body power was measured using the chest medicine ball throw test, and the data were analyzed using paired t-tests to examine within-group differences and independent t-tests to compare between groups. Result: Paired t-test results showed a significant increase in power within both groups (p<0.05). However, independent t-test results indicated a statistically significant difference between the intervention and control groups (p = 0,002; p < 0,05), with the intervention group showing a greater increase in power. Conclusion: These findings suggest that caffeine consumption positively impacts the power performance of wrestling athletes. Based on this study, it is suggested that strategic caffeine supplementation may serve as a more effective approach in supporting overall athletic performance.